2022
DOI: 10.1186/s12913-022-07990-8
|View full text |Cite
|
Sign up to set email alerts
|

Exploring how to enhance care and pathways between the emergency department and integrated youth services for young people with mental health and substance use concerns

Abstract: Background Integrated youth services (IYS) provide multidisciplinary care (including mental, physical, and social) prioritizing the needs of young people and their families. Despite a significant rise in emergency department (ED) visits by young Canadians with mental health and substance use (MHSU) concerns over the last decade, there remains a profound disconnect between EDs and MHSU integrated youth services. The first objective of this study was to better understand the assessment, treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…This impedes motivation to engage in mental health aftercare. Repeating the same stories to multiple clinicians may also be another source of frustration 51 . Young people may be less inclined to attend the follow-up appointment if they expect themselves to be repeating the difficult and negative experiences that resulted in their A&E presentation.…”
Section: Discussionmentioning
confidence: 99%
“…This impedes motivation to engage in mental health aftercare. Repeating the same stories to multiple clinicians may also be another source of frustration 51 . Young people may be less inclined to attend the follow-up appointment if they expect themselves to be repeating the difficult and negative experiences that resulted in their A&E presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Repeating the same stories to multiple clinicians may also be another source of frustration. 51 Young people may be less inclined to attend the follow-up appointment if they expect themselves to be repeating the di cult and negative experiences that resulted in their A&E presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Chart records for these data exposed substantial challenges and gaps in the continuity of care between our community‐based IYS setting and those acute care settings. Such challenges have been described in a recent qualitative study that sought to understand how youth with mental health and substance use concerns are assessed and treated in emergency departments (Glowacki et al, 2022). In this study, Glowacki et al (2022) identified several gaps in the quality of care for youth in the emergency department setting, such as inappropriate assessments, long waiting times in a stressful environment, and inadequate discharge and referral pathways (Glowacki et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Such challenges have been described in a recent qualitative study that sought to understand how youth with mental health and substance use concerns are assessed and treated in emergency departments (Glowacki et al, 2022). In this study, Glowacki et al (2022) identified several gaps in the quality of care for youth in the emergency department setting, such as inappropriate assessments, long waiting times in a stressful environment, and inadequate discharge and referral pathways (Glowacki et al, 2022). Given these findings and the ongoing overdose crisis, it is critical that policy makers develop interventions or programs for the acute care setting that are tailored to the needs of youth using substances, including those from racialized or sexual and gender minority populations, and promote continuity between healthcare settings through addressing the above gaps in care quality.…”
Section: Discussionmentioning
confidence: 99%